Associations between Stroke Mortality and Weekend Working by Stroke Specialist Physicians and Registered Nurses: Prospective Multicentre Cohort Study - Bray, Benjamin D. (Public Library of Science, 2014)
BACKGROUND: Observational studies have reported higher mortality for patients admitted on weekends. It is not known whether this “weekend effect” is modified by clinical staffing levels on weekends. We aimed to test the hypotheses that rounds by stroke specialist physicians 7 d per week and the ratio of registered nurses to beds on weekends are associated with mortality after stroke. METHODS AND FINDINGS: We conducted a prospective cohort study of 103 stroke units (SUs) in England. Data of 56,666 patients with stroke admitted between 1 June 2011 and 1 December 2012 were extracted from a national register of stroke care in England. SU characteristics and staffing levels were derived from cross-sectional survey. Cox proportional hazards models were used to estimate hazard ratios (HRs) of 30-d post-admission mortality, adjusting for case mix, organisational, staffing, and care quality variables. After adjusting for confounders, there was no significant difference in mortality risk for patients admitted to a stroke service with stroke specialist physician rounds fewer than 7 d per week (adjusted HR [aHR] 1.04, 95% CI 0.91–1.18) compared to patients admitted to a service with rounds 7 d per week. There was a dose–response relationship between weekend nurse/bed ratios and mortality risk, with the highest risk of death observed in stroke services with the lowest nurse/bed ratios. In multivariable analysis, patients admitted on a weekend to a SU with 1.5 nurses/ten beds had an estimated adjusted 30-d mortality risk of 15.2% (aHR 1.18, 95% CI 1.07–1.29) compared to 11.2% for patients admitted to a unit with 3.0 nurses/ten beds (aHR 0.85, 95% CI 0.77–0.93), equivalent to one excess death per 25 admissions. The main limitation is the risk of confounding from unmeasured characteristics of stroke services. CONCLUSIONS: Mortality outcomes after stroke are associated with the intensity of weekend staffing by registered nurses but not 7-d/wk ward rounds by stroke specialist physicians. The findings have implications for quality improvement and resource allocation in stroke care. Please see later in the article for the Editors' Summary